Antecedents and consequences of internal crisis communication in Malaysian high-risk industry: a framework and agenda for future research. (31st August 2022) - Mohamad, Bahtiar; Adamu, Adamu Abbas; Halim, Haslina
In crisis management research, internal crisis communication (ICC) has been identified to be a new area of study. In fact, extant literature has indicated a lack of theoretical development on the dimensions of ICC. This paper aims to make provision accordingly for conceptual clarity on ICC in order to unfold its underlying antecedents and consequences from the employees' perspectives in Malaysia high-risk industry through a proposed conceptual framework. Although, it is consolidated that important roles are being played by ICC in strategic management planning as there exists high relevance of managing positive relationship significantly between multiple stakeholders and corporate survival. Following a critical and comprehensive review of multidisciplinary literature using conceptual approach, a model is finally developed. Four antecedents are identified from the outcomes of this study: safety culture, supportive environment, social media perceived usefulness and management commitment. A potential positive relationship is highlighted between ICC, perceived organisational support and affective commitment.